Dampak Kualitas Produk, Harga dan Word Of Mouth terhadap Minat Beli pada Butik Islamiyah Taqwa Travel Palembang - Aidil Fitriansyah; Nuraida Nuraida; Emi Puspita Dewi (ScidacPlus, 2024)
The impact on income is due to efforts to improve product quality and price again so as to create a good image for the company, so the researchers determined the title